A Case Report of Amyotrophic Lateral Sclerosis Presented As Dysarthria and Dysphagia - Assistant Professor Dr. Aaemal “Aziz Jabarkhil; Assistant Professor Dr. Abdul Hanan “Safi”; Assistant Professor Dr. Aziz Rahman “Rasib”; Ali Abad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Amyotrophic lateral sclerosis is a fatal and rare disease of the motor neuron system, caused by the degeneration of the motor neuron and featured by a progressive muscular palsy. This condition gradually progresses and cause spasticity, weakness and wasting of the muscles. This condition can affect gait. The incidence of ALS in different population ranges from one-two cases per 100,000 people per year. Clinical features caused by this condition in upper and lower extremities are more obvious than other types of paralysis caused by other conditions. Major clinical manifestation of MND include dysphagia that cause decreased survival and quality of life. Dysarthria and dysphagia of amyotrophic lateral sclerosis caused by involvement of medulla that in 1/3 cases seen in early stage of the disease. Reevaluation for the dysphagia conclude the history, clinical examination, electromyography, nerve condition velocity and video fluoroscopy swallow study and some other conditions such as cervical spondylosis, myelopathies, multifocal motor neuropathy space occupying lesion, stroke and other related pathology should be excluded. The average life span for this condition is 2-5 years. Treatment is multi-disciplinary as conservative and supportive. Physiotherapy for increased of ability and drug Riluzole is used for prevention of progressive course of this disease are advised. Noninvasive ventilation may increase the span and quality of life. We here report a case of 55 years old lady with dysphagia, dysarthria and muscular cramps since 18 months with gradually progressive course, whom previously was treated for conditions such as ischemic stroke, gastritis, esophagitis and mental conditions, but with help of good clinical evaluation and laboratory exams such as electromyography, nerve conduction velocity, this condition is diagnosed and reported.